2000
DOI: 10.4319/lo.2000.45.5.1187
|View full text |Cite
|
Sign up to set email alerts
|

The exopolymer secretions (EPS) layer surrounding Aureoumbra lagunensis cells affects growth, grazing, and behavior of protozoa

Abstract: Abstract-''Texas brown tide'', a nuisance algal bloom formed by the marine pelagophyte Aureoumbra lagunensis, persisted without interruption from 1990-1997 in Laguna Madre, Texas. We hypothesize that, in addition to other factors, the presence of a mucus layer of exopolymer secretions (EPS) outside its cell wall may have played a role in reducing microzooplankton grazing on A. lagunensis, and therefore contributing to the persistence of the brown tide bloom. Three protozoan species common to the bloom waters f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 13 publications
(30 reference statements)
2
49
0
Order By: Relevance
“…Other researchers have suggested that the excretion of mucous by algae provide advantages in terms of nutrient availability, competition with other phytoplankton species and reduction of grazing losses (Reynolds 2006). The presence of large quantities of mucilage may also contribute to observed negative impacts of A. sanguinea on other plankton, pelagic fauna and benthic organisms, as observed for other mucous producing algal species (Shumway 1990, Buskey & Hyatt 1995, Liu & Buskey 2000, Botes et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have suggested that the excretion of mucous by algae provide advantages in terms of nutrient availability, competition with other phytoplankton species and reduction of grazing losses (Reynolds 2006). The presence of large quantities of mucilage may also contribute to observed negative impacts of A. sanguinea on other plankton, pelagic fauna and benthic organisms, as observed for other mucous producing algal species (Shumway 1990, Buskey & Hyatt 1995, Liu & Buskey 2000, Botes et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, less desirable species of phytoplankton may experience lower predation rates and these phytoplankton may be assumed to include less nutritious, noxious or toxic algal taxa. In support of this argument, poor nutritional quality and exopolymer excretions have been demonstrated as factors contributing to the dominance of the Texas brown tide alga Aureoumbra lagunensis in Laguna Madre, Texas (Buskey et al 1997, Liu & Buskey 2000.…”
Section: Introductionmentioning
confidence: 89%
“…L 21 demonstrated to be the threshold for negative effects. Because the mesoflagellate-derived TEP consisted mainly of free particles, differences in exopolymer secretions, generally associated with cells and known to affect grazers (Liu and Buskey 2000), can also be excluded as a mechanism for the avoidance of some strains. Similarly, we did not find any evidence for toxin excretion by P. globosa.…”
Section: Discussionmentioning
confidence: 99%